The Combination of Online Media in Islamic Religious Education Learning for Students at Islamic Middle School in Karawang - Amalia Firdausya Nurbaeti; Sutarjo Sutarjo; Lilis Karyawati (Edumaspul: Jurnal Pendidikan, 2022)
The current Covid-19 pandemic has spread in Indonesia and has become the most frightening disease for the wider community. During the COVID-19 pandemic, the education sector in Indonesia used an online learning system and all work was carried out by means of Work From Home (WFH). A term that is now being suggested by the government as a social distancing tactic, even religious activities are closed because crowded places are vulnerable. and easy for the spread of the covid-19 virus Education. This study aims to determine the use of online media in learning Islamic religious education at Islamic Middle School Karawang. The approach used is qualitative research by using data collection techniques in the form of observation and interviews. The results in this study indicate that, in learning Islamic Religious Education at SMP Islam Karawang using online media, namely using Zoom Cloud Meeting, Youtube and WhatsApp. The combination of these three online media is used for the root learning process in Islamic Religious Education (PAI) learning. Regarding this online media integration, Islamic Religious Education (PAI) teachers feel they can make learning more effective because each online media used has different uses.